Molecular medicine: a path towards a personalized medicine - Miranda,Debora Marques de (2012)
Psychiatric disorders are among the most common human illnesses; still, the molecular and cellular mechanisms underlying their complex pathophysiology remain to be fully elucidated. Over the past 10 years, our group has been investigating the molecular abnormalities in major signaling pathways involved in psychiatric disorders. Recent evidences obtained by the Instituto Nacional de Ciência e Tecnologia de Medicina Molecular (National Institute of Science and Technology - Molecular Medicine, INCT-MM) and others using behavioral analysis of animal models provided valuable insights into the underlying molecular alterations responsible for many complex neuropsychiatric disorders, suggesting that "defects" in critical intracellular signaling pathways have an important role in regulating neurodevelopment, as well as in pathophysiology and treatment efficacy. Resources from the INCT have allowed us to start doing research in the field of molecular imaging. Molecular imaging is a research discipline that visualizes, characterizes, and quantifies the biologic processes taking place at cellular and molecular levels in humans and other living systems through the results of image within the reality of the physiological environment. In order to recognize targets, molecular imaging applies specific instruments (e.g., PET) that enable visualization and quantification in space and in real-time of signals from molecular imaging agents. The objective of molecular medicine is to individualize treatment and improve patient care. Thus, molecular imaging is an additional tool to achieve our ultimate goal.